Autoimmune Addison's disease - Saverino, Serena; Falorni, Alberto (Baillière's best practice & research. Clinical endocrinology & metabolism, 2020)
Primary adrenal insufficiency (PAI) occurs in 1/5000–1/7000 individuals in the general population. Autoimmune Addison's disease (AAD) is the major cause of PAI and is a major component of autoimmune polyendocrine syndrome type 1 (APS1) and type 2 (APS2). Presence of 21-hydroxylase autoantibodies (21OHAb) identifies subjects with ongoing clinical or pre-clinical adrenal autoimmunity. AAD requires life-long substitutive therapy with two-three daily doses of hydrocortisone (HC) (15–25 mg/day) or one daily dose of dual-release HC and with fludrocortisone (0.5–2.0 mg/day). The lowest possible HC dose must be identified according to clinical and biochemical parameters to minimize long-term complications that include osteoporosis and cardiovascular and metabolic alterations. Women with AAD have lower fertility and parity as compared to age-matched healthy controls. Patients must be educated to double-triple HC dose in the case of fever or infections and to switch to parenteral HC in the case of vomiting, diarrhoea or acute hypotension.